2020
DOI: 10.1093/deafed/enz046
|View full text |Cite
|
Sign up to set email alerts
|

Reading and Theory of Mind in Adolescents with Cochlear Implant

Abstract: Previous research has shown a possible link between reading comprehension and theory of mind (ToM), but these findings are unclear in adolescents with cochlear implants (CI). In the present study, reading comprehension and ToM were assessed in adolescents with CI and the relation between both skills was also studied. Two sessions were performed on two groups of adolescents aged between 12 and 16 years of age (36 adolescents with CI and 54 participants with typical hearing, TH). They were evaluated by means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
3
11
0
Order By: Relevance
“…Regarding the reading performance of the CI group, this was significantly lower in comparison with TH. Our results are in line with previous studies concerning low reading comprehension in adolescents with CI (Dillon et al, 2012; Figueroa et al, 2020). In addition, the analysis of the performance on different types of questions suggested that the CI group performed poorly on literal questions of mnemonic comprehension and on inferential questions of non-mnemonic reading comprehension.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the reading performance of the CI group, this was significantly lower in comparison with TH. Our results are in line with previous studies concerning low reading comprehension in adolescents with CI (Dillon et al, 2012; Figueroa et al, 2020). In addition, the analysis of the performance on different types of questions suggested that the CI group performed poorly on literal questions of mnemonic comprehension and on inferential questions of non-mnemonic reading comprehension.…”
Section: Discussionsupporting
confidence: 93%
“…Weaknesses in these EF could have a negative effect on different academic domains such as studying, test-taking, long-term projects, written expression, or reading comprehension (Meltzer & Krishnan, 2007). CI have provided linguistic and academic improvements for children with hearing loss (Geers & Nicholas, 2013; Schorr et al, 2008), but some studies have shown that these improvements are not enough for them to understand a text at the same level as their TH peers in adolescence (Dillon et al, 2012; Figueroa et al, 2020). However, Geers and Hayes (2011) reported that most adolescents with CI were within or above the average range for their hearing peers in reading skills scores.…”
mentioning
confidence: 99%
“…This early discrepancy in FBU might also persist in adolescents with CIs, as reported by Figueroa et al. (2020) .…”
Section: Introductionmentioning
confidence: 70%
“…Delay in false belief understanding might also affect the development of advanced ToM concepts, as suggested by the recent study of Figueroa et al [75]. They showed that deaf adolescents aged 12-16 years with CIs had a lower understanding of second-or higher-order beliefs and of understanding multiple perspectives requiring mentalizing.…”
Section: Tom Development In Deaf Children With Cismentioning
confidence: 94%